Small molecules, peptides and natural products: getting a grip on 14-3-3 protein-protein modulation - Bartel, Maria; Schäfer, Anja; Stevers, Loes M; Ottmann, Christian (Future medicinal chemistry, 2014)
One of the proteins that is found in a diverse range of eukaryotic protein-protein interactions is the adaptor protein 14-3-3. As 14-3-3 is a hub protein with very diverse interactions, it is a good model to study various protein-protein interactions. A wide range of classes of molecules, peptides, small molecules or natural products, has been used to modify the protein interactions, providing both stabilization or inhibition of the interactions of 14-3-3 with its binding partners. The first protein crystal structures were solved in 1995 and gave molecular insights for further research. The plant analog of 14-3-3 binds to a plant plasma membrane H(+)-ATPase and this protein complex is stabilized by the fungal phytotoxin fusicoccin A. The knowledge gained from the process in plants was transferred to and applied in human models to find stabilizers or inhibitors of 14-3-3 interaction in human cellular pathways.